Comparison of Dissolution Profiles of Formulations Containing Ferrous Sulfate and Fumarate - Basulado, S. (2012)
The aim of the present study was to evaluate and compare the dissolution profiles of seven commercial products con- taining ferrous sulfate and fumarate marketed in Argentina, based on their in vitro dissolution characteristics using USP Apparatus 2.